Quasi-Cauchy Sequences on Asymmetric Metric Spaces - DAĞCI, FİKRİYE İNCE; Çakallı, Hüseyin (Univ Nis, Fac Sci Math, 2024)
In recent years, quasi-Cauchy sequences have been studied by many authors in the real line and in metric spaces. In this paper, we investigate the concepts of quasi Cauchyness of sequences, ward compactness and ward continuity in asymmetric metric spaces. We prove that forward totally boundedness coincides with upward compactness, backward totally boundedness coincides with downward compactness, an upward continuous function on a subset E of an asymmetric metric space X to an asymmetric metric space Y is forward continuous under the condition that forward convergence implies backward convergence on X. We also prove some other interesting theorems.